PARP1 is activated by membrane damage and is involved in membrane repair through poly(ADP‐ribosyl)ation. (21st February 2022) - Mashimo, Masato; Kita, Momoko; Nobeyama, Akari; Nomura, Atsuo; Fujii, Takeshi
Abstract: Mono(ADP‐ribosyl)ation and poly(ADP‐ribosyl)ation are posttranslational modifications evolutionarily conserved in prokaryotes and eukaryotes. They entail transfer of one or more ADP‐ribose moieties from NAD + to acceptor proteins with the simultaneous release of nicotinamide. The resultant ADP‐ribosylated acceptor proteins regulate diverse cellular functions. For instance, ADP‐ribosyltransferase 1 (ART1) catalyzes mono(ADP‐ribosyl)ation of arginine residues in Trim72, a protein specifically expressed in muscle cells and involved in cell membrane repair, which is enhanced upon its ADP‐ribosylation. By contrast, the contribution made by ADP‐ribosylation to membrane repair in epithelial cells remains unclear. In this study, we investigated the involvement of ADP‐ribosylation in cell membrane repair in HEK293T and HeLa cells. We found that upon induction of membrane damage using streptolysin‐O, poly(ADP‐ribose) polymerase 1 (PARP1) catalyzed poly(ADP‐ribosyl)ation. In scratch assays, inhibition of PARP1 activity using the nonspecific PARP inhibitor PJ34 or shRNA targeting PARP1 delayed wound healing, suggesting that PARP1‐catalyzed poly(ADP‐ribosyl)ation plays a key role in membrane repair in epithelial cells. Abstract : Upon membrane damage, PARP1 generates poly(ADP‐ribose) (PAR), involved in membrane repair.